The Implementation Analysis of Total Quality Management in Clothing Sewing Training - Nailufar, Nina; Ekosiswoyo, Rasdi; Mulyono, Sungkowo Edy (Journal of Nonformal Education, 2019)
The new paradigm in the era of globalization of education is to prioritize the quality and relevance of education to support global competition, so that the application of the Total Quality Management model in the training program and the achievement of service quality dimension in education is the implementation step of Total Quality Management. The purposes of this study to analyze and describe the application of Total Quality Management models, the quality dimensions of training services as a form of customer satisfaction achievement of Sewing Training at the Balai Latihan Kerja Dinas Tenaga Kerja, Perindustrian, Koperasi Usaha Kecil dan Menengah Kabupaten Kudus. This research used qualitative descriptive approach method with direct research data source on research subject by using snowballing sampling method. Technique of collecting research data through interview, observation, Focus Group Discussion, documentation. The results of this study describe that the Deming model, Crosby model, and Juran Model were implemented in training programs. The conclusion of this study describes the implementation of Total Quality Management in the training program applies various models of Total Quality Management, carried out continuously to improve the quality of training implementation and achieve customer satisfaction through the achievement of the quality dimension of training services.